Pengaruh Affiliate Marketing, Content Marketing dan Live Streaming Terhadap Keputusan Pembelian Produk Lunafore di E-Commerce - Siti Nurjanah; Ridho Riadi Akbar (IKRAITH-EKONOMIKA, 2025)
This research is designed to examine the extent to which digital marketing strategies shape consumers purchase decisions for Lunafore products in online marketplaces. The analysis concentrates on three core variables, namely affiliate marketing, content marketing, and live streaming. A quantitative research framework was employed by integrating descriptive and verificative methods to ensure robust empirical assessment. Data were collected through an online Likert-scale questionnaire distributed to 100 internet users selected using purposive sampling techniques. The collected responses were subsequently analyzed using multiple linear regression to evaluate the relationships among variables. The empirical results reveal that live streaming, content marketing, and affiliate marketing each exert a positive and statistically significant effect on consumers’ purchasing decisions. Furthermore, the simultaneous testing indicates that these three variables jointly explain 62.6% of the variance in purchase decisions. These findings highlight the strategic importance of adopting an integrated digital marketing approach to strengthen consumer purchase behavior within e-commerce environments.